Emission study on dimethyl ether-biodiesel blends fuelled diesel engine. Issue 1 (31st December 2022) - Sajin, Justin Abraham Baby; Paul, Christu; Ratheesh, R.; Vijayan Pillai, Akhil Kunnel; Rathinam, Sivasubramanian
ABSTRACT: The emission characteristics of, single-cylinder, four-stroke, water-cooled diesel engine fuelled with two blends of DME (Dimethyl ether) and biodiesel i.e. DME10BD90 and DME20BD80 (10% and 20% volume of DME blended in 90% and 80% volume of BDF) and Pongamia biodiesel (BDF) at the compression ratio 17.5:1 were explored. The base-catalyzed transesterification process was used for Pongamia biodiesel production with the presence of methanol and catalyst (KOH). Experimental results exposed that the CO and HC reduced with DME blending to Pongamia biodiesel. In addition, the diesel engine when fuelled with DME10BD90 and DME20BD80, reduced Smoke and NOX emissions, significantly than Pongamia biodiesel.